The influence of the modifying elements on the microstructure, mechanical, and deformation properties of aluminum alloys - Alzahrani, Mahmoud A.; Moustafa, Essam B.; Alsoruji, Ghazi; Mosleh, Ahmed O. (Frontiers in Materials, 2022)
In the current work, the standard A242 aluminum cast alloy is modified using the stir cast method with Titanium Ti (0.5%wt.) and Boron B(0.1%wt.) modifiers. The effect of the refining elements on the modified alloys A242+TiB is evaluated using polarized optical and scanning electron microscopy; thus, the Ti-B modifiers cause a refinement in the microstructure grain by ~13.5 times the as-cast alloy. The mechanical properties are investigated experimentally using tensile and compression tests in addition to the hardness test; the results revealed that the ultimate and compressive strengths of the A242+TiB modified alloy are increased by 20% more than A242 standard alloy. The dynamic properties are performed using a free vibration impact test to study the modifiers' effect on the dynamic behavior. The grain refinement notably impacts the damping capacity; due to as-cast inhomogeneity, the conventional alloy A242 has a greater FRF than the improved alloy A242+TiB. The modified alloy displays fewer resonance peaks due to grain refinement and excellent intermetallic phase distribution. The simulation process of the investigated alloys is performed using ABAQUS finite element software to predict the deformation behavior under different temperatures. The FE results show that A242+TiB is 7.1% more resistant to deformation than A242 at room temperature and 6.6% at 250Co.